Improving timeliness of lung cancer care through a rapid assessment clinic - Shakti V. Dabholkar; Shalini Vinod; Zinta Harrington; Benjamin Kolevski; Beth Ivimey; Joseph Descallar; Jonathan P. Williamson (Internal Medicine Journal, 2026)
Abstract Background Early diagnosis and treatment of lung cancer improve survival. Guidelines from Australia and worldwide stipulate timeframes of care from referral. The Rapid Lung Assessment Clinic (RLAC) was established to fast‐track the diagnostic and treatment pathway, with a subsequent quality improvement initiative based on the initial analysis of timeliness of care. Aim This study evaluated the performance of RLAC before and after the quality improvement initiative and identified patient and system factors, which affect timeliness of care. Methods This was a retrospective, observational cohort study evaluating RLAC. The clinic was established in 2018 as a weekly clinic serviced by respiratory physicians associated with the hospital's lung cancer multidisciplinary team. In 2020, the service gained access to a dedicated nurse coordinator who organised pre‐clinic positron emission tomography scan and/or other investigations prior to clinic appointment. Results Median times from referral to specialist review (11 vs 10 days, P = 0.02 (before vs after intervention)), diagnosis (28 vs 21 days, P = 0.5) and treatment (63 vs 51 days, P = 0.001) were all reduced after intervention. Before and after the intervention, 71% (before intervention) versus 74% (after intervention) of patients had specialist review within 14 days, and 29% versus 40% commenced treatment within 42 days. Earlier stage of disease, need for surgical treatment and greater number of diagnostic investigations was associated with longer times to treatment. Conclusion Our intervention reduced delays to treatment of lung cancer in a rapid assessment clinic. The majority of patients were still not treated within recommended timeframes, raising the question of whether guideline timeframes are realistic given the modern‐day complexities of lung cancer work‐up.